Immunohistochemical evidence for the derivation of a peptide ligand from the amyloid beta-protein precursor of Alzheimer disease. - Allsop, D (1988)
A monoclonal antibody to a synthetic peptide consisting of residues 8-17 of the amyloid beta protein of Alzheimer disease was used in immunohistochemical studies to reveal binding sites for this peptide in vesicular elements in the islets of Langerhans of the pancreas and the zona reticularis of the adrenal gland. These binding sites may represent a specific membrane receptor. These results, together with similarities in structural features between the precursors for epidermal growth factor and beta protein, suggest that the beta-protein precursor may be processed to release an active peptide ligand rather than acting as a membrane receptor. In Alzheimer disease, abnormal processing of this active peptide precursor may result in the deposition of beta-protein amyloid fibrils in the brain.